ENTRAVES PARA O FUNCIONAMENTO DOS COMITÊS DE INTEGRAÇÃO FRONTEIRIÇA: O CASO CORUMBÁ-PUERTO SUÁREZ - Vitorino José Barros da Silva (2022)
The interactions among government actors of the different levels and their correlations with the border society aiming at the creation of national and bilateral public policies in the context of the Border Integration Committee Corumbá-Puerto Suárez will be under investigation in this study. Border committees are mechanisms for dialogue on local problems as well as instruments for proposing and implementing solutions for border demands, and their regular functioning can represent integration and development for border regions. Given the importance of these committees, the objective of this study is to understand why the Border Integration Committee Corumbá-Puerto Suárez does not function with satisfactory regularity. In addition, the research proposes to outline the intra-governmental and inter-state interactions related to the events of the bilateral dialogue mechanism. In order to achieve these objectives, diplomatic cables were collected through access to Itamaraty's internal database, and, upon direct request to this ministry, other documents that referred to the efforts of articulation, stance taking, meetings and its results were also obtained. The analysis of this corpus was based on theories that focus on the international activity of subnational entities, multilayered diplomacy, social concertation, and polycentric systems of governance. After analysis, it was observed that, even though the central government makes room in the agendas for recommendations of the border actors, it tends to assume a hierarchically superior position in conducting the dialogues and, therefore, the meetings and the implementation of the solutions depend too much on its disposition, restricting the collaboration of local agents that truly experience the border reality. Based on these findings, the study proposes a working model in which a local border committee, articulated in a polycentric system of governance with other governmental levels and with the border community, becomes the starting point of resolutions referring to the border region.